2017
DOI: 10.1021/acs.est.6b05576
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Bisolute Adsorption of Aromatic Compounds Based on Adsorbed Solution Theories

Abstract: A large number of organic contaminants are commonly found in industrial and municipal wastewaters. For proper unit design to remove contaminant mixtures by adsorption, multicomponent adsorption equilibrium models are necessary. The present work examined the applicability of Ideal Adsorbed Solution Theory (IAST), a prevailing thermodynamic model, and its derivatives, i.e., Segregated IAST (SIAST) and Real Adsorbed Solution Theory (RAST), to bisolute adsorption of organic compounds onto a hyper-cross-linked poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…Other examples of the failure of the IAST, along with alternative approaches to RAST modeling of non-idealities, are available in the literature. , …”
Section: Resultsmentioning
confidence: 99%
“…Other examples of the failure of the IAST, along with alternative approaches to RAST modeling of non-idealities, are available in the literature. , …”
Section: Resultsmentioning
confidence: 99%
“…The single isotherms were fitted with different adsorption isotherm models, including Langmuir, Freundlich, and the quadratic equation used in our previous research. 40 The best-fitting model was selected as the working isotherm, and the best-fitting parameters were then used to calculate the adsorbed amounts in bisolute adsorption. The AST equations (Text S2 and eqs S5−S9) were solved in Matlab 2019a (details of the code and input data setup are given in Texts S2 and S3).…”
Section: ■ Model Developmentmentioning
confidence: 99%
“…In our previous research, 40 pp-LFERs helped build MLR models for the activity coefficients in bisolute adsorption under infinite dilute conditions and provided predictions for several bisolute mixtures. The results indicated that pp-LFERs are helpful in capturing interactions between different adsorbed solutes.…”
Section: ■ Model Developmentmentioning
confidence: 99%